Disowning Imperialism and Remembering Dhaka University in A.G. Stock’s Travelogue - Alam, Zerin (Spectrum, 2022)
Memoirs of Dacca University is the record of a British teacher’s experience of being Head of the English Department at the transitional time of 1947 to 1951. The traveller’s focus on Dhaka University makes it a valuable historic document of the institution in her depiction of the challenges of English language teaching in a former colony. The aim of this article is to analyze A. G. Stock’s memoir as an example of post-imperial travelogue and to examine the traveller’s attempts to overcome colonial representations in her treatment of Dhaka University and the people she encounters. I show how Stock’s text differs from colonial travel writing and embraces a more empathetic and liberal view in her analysis and description of the university and East Pakistan. At the same time, following Holland and Huggan (2000), I also interrogate and trace the lingering residues of a colonial discourse in this travel narrative. Spectrum, Volume 16, June 2021: 24-39